The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000113932
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha and Interleukin-10 in Whole Blood Is Associated with Disease Progression in Pulmonary Mulitdrug-Resistant Tuberculosis Patients

Abstract: Background: Cytokine production profiles may reflect the clinical pictures of patients with tuberculosis (TB). Objective: We examined the relationship between cytokine levels and clinical parameters indicating the state of disease in active pulmonary TB patients. Methods: We measured interferon (IFN)-γ, tumor necrosis factor (TNF)-α and interleukin (IL)-10 levels in whole blood after stimulation with culture filtrate protein of Mycobacterium tuberculosis in 33 multi-drug resistant (MDR)-TB and 51 non-MDR-TB pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
11
0
4
Order By: Relevance
“…In this study, we build upon our previous findings that TNF-α, IFN-γ and IL-10 profiles are distinct in non-MDR-TB versus MDR-TB patients [5]. Using sputum clearance as an indicator of positive responses to chemotherapies, we report that patients on anti-Mtb chemotherapies have altered TNF-α and IFN-γ levels that correlate with favorable responses to the drugs.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In this study, we build upon our previous findings that TNF-α, IFN-γ and IL-10 profiles are distinct in non-MDR-TB versus MDR-TB patients [5]. Using sputum clearance as an indicator of positive responses to chemotherapies, we report that patients on anti-Mtb chemotherapies have altered TNF-α and IFN-γ levels that correlate with favorable responses to the drugs.…”
Section: Introductionmentioning
confidence: 76%
“…Cytokine production patterns in TB patients are presumed to vary according to the disease state, and we have previously reported that TNF-α was associated with MDR-TB and mycobacterial load in sputum [5]. However, our previous study was cross-sectional, limiting our ability to evaluate these correlations as markers to potentially predict outcome.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Further, antigen-specific IL-10 production is found in pulmonary TB patients (341, 342) and along with TNF-α production can be used to reliably distinguish between latent TB and pulmonary TB (342). In addition, increased accumulation of T REGS expressing IL-10 correlates with increased bacterial burden and more severe TB in an Indian population (343, 344) and a high level of IL-10 at the end of treatment in pulmonary TB patients is associated with TB recurrence (345). Finally, infection with helminths in TB patients results in decreased antigen-specific IFNγ and IL-17 responses, which is dependent on IL-10, as IL-10 blockade significantly increases frequencies of IFNγ producing cells (346, 347).…”
Section: Cytokinesmentioning
confidence: 99%